Validation of Gene Therapy for Mutant Mitochondria by Delivering Mitochondrial RNA Using a MITO-Porter - Eriko Kawamura; Minako Maruyama; Jiro Abe; Akira Sudo; Atsuhito Takeda; Shingo Takada; Takashi Yokota; Shintaro Kinugawa; Hideyoshi Harashima; Yuma Yamada (Elsevier, 2020)
Here, we report on validating a mitochondrial gene therapy by delivering nucleic acids to mitochondria of diseased cells by a MITO-Porter, a liposome-based carrier for mitochondrial delivery. We used cells derived from a patient with a mitochondrial disease with a G625A heteroplasmic mutation in the tRNAPhe of the mitochondrial DNA (mtDNA). It has been reported that some mitochondrial gene diseases are caused by heteroplasmic mutations, in which both mutated and wild-type (WT) genes are present, and the accumulation of pathological mutations leads to serious, intractable, multi-organ diseases. Therefore, the decrease of the mutated gene rate is considered to be a useful gene therapy strategy. To accomplish this, wild-type mitochondrial pre-tRNAPhe (pre-WT-tRNAPhe), prepared by in vitro transcription, was encapsulated in the MITO-Porter. The pre-WT-tRNAPhe encapsulated in the MITO-Porter was transfected into diseased mitochondrial cells, and the resulting mutant levels were examined by an amplification refractory mutation system (ARMS)-quantitative PCR. The mutation rate of tRNAPhe was decreased, and this therapeutic effect was sustained even on the 8th day after transfection. Furthermore, mitochondrial respiratory activity of the disease cells was increased after the transfection of therapeutic pre-WT-tRNAPhe. These results support the conclusion that the mitochondrial delivery of therapeutic nucleic acids represents a viable strategy for mitochondrial gene therapy.